Computer Simulations of Traffic on Road Intersections. - Provido, Eden Delight B.
This study developed a model and implemented a simulation of a typical Metro Manila intersection. The simulation is implemented in serial programming using JAVA. Two-dimensiona four-segment intersections and deterministic and stochastic cellular automata models with non-periodic boundary conditions are employed. Results show that the intersection models developed satisfy the theoretical assumptions of the classical theory of traffic dynamics.
Keywords: Traffic Dynamics; Cellular automata; Computer Modeling and Simulation; Java